Characteristics of patients hospitalized for COVID-19 in the La Libertad–EsSalud healthcare network, 2020 - Alfaro Angulo, Marco Antonio (2021)
Objective: To describe the characteristics of patients hospitalized for COVID-19 in the La Libertad–EsSalud healthcare network, 2020. Materials and methods: A descriptive study. The data was collected from the clinical epidemiological records and medical records of patients hospitalized from March 15 to August 17, 2020. The research variables were age, sex, comorbidity, hospital stay, use of mechanical ventilation, number of days on mechanical ventilation, number of deaths and number of discharged patients. Absolute and relative frequencies and the p value were calculated. Results: The study population consisted of 2,093 patients hospitalized for COVID-19, whose average age was 58 years. Sixtyone point two three percent (61.23 %) were males, 39.99 % had comorbidities, the mean hospital stay was 8 days, 9.79 % were admitted to the ICU and spent 20.40 days on average, 9.56 % required mechanical ventilation, 40.28 % of the total number of patients died, 54.50 % of those who received mechanical ventilation died, and 49.74 % were discharged. Conclusions: The average age of the patients was 58 years, most of whom were males. The main comorbidities were high blood pressure, diabetes and obesity. The average hospital stay was 8.02 days, 9.79 % of the patients were admitted to the ICU, 9.56 % required mechanical ventilation, 40.28 % died, 54.50 % of those who received mechanical ventilation died, and 49.74 % were discharged.